2008
DOI: 10.1136/tc.2007.023689
|View full text |Cite
|
Sign up to set email alerts
|

Existing technologies to reduce specific toxicant emissions in cigarette smoke

Abstract: Technologies exist to reduce the toxicants identified by TobReg. The extent to which the industry is able to simultaneously reduce toxicants, however, is unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 54 publications
(52 reference statements)
0
21
0
Order By: Relevance
“…Some smoke component emission levels may be lowered by adapting agricultural practices, plant characteristics, tobacco blending, and cigarette design (for example additives, filters, papers) [44]. For instance, parameters which influence heavy metal concentration in tobacco include growing conditions (e.g., soil type and pH), agricultural practices (e.g., use of metal-containing pesticides and fertilizers), genotype, stalk position, and processing of tobacco leaves [45].…”
Section: Resultsmentioning
confidence: 99%
“…Some smoke component emission levels may be lowered by adapting agricultural practices, plant characteristics, tobacco blending, and cigarette design (for example additives, filters, papers) [44]. For instance, parameters which influence heavy metal concentration in tobacco include growing conditions (e.g., soil type and pH), agricultural practices (e.g., use of metal-containing pesticides and fertilizers), genotype, stalk position, and processing of tobacco leaves [45].…”
Section: Resultsmentioning
confidence: 99%
“…The per cigarette basis is derived mathematically from the per mg basis, e.g., the results per mg of tar multiplied by the tar yield from the whole cigarette. More recently, yields per mg of nicotine have been considered, which also is a mathematically derived result, but in this case the results of the yield per mg tar is extrapolated to the nicotine content determined in a separate assay (97). There are rationales, merits and limitation for all these methods.…”
Section: Resultsmentioning
confidence: 99%
“…In 2009, O'CONNOR and HURLEY (17) re-investigated and interpreted the data of PHILLPOTTS et al (16) differently.…”
Section: Discussionmentioning
confidence: 99%
“…In 1975, PHILLPOTTS et al (16) reported no correlation between the total aldehyde yields in cigarette mainstream smoke and tobacco blend sugar contents of 83 commercial European brands. Some authors (17) have recently re-interpreted the PHILLPOTTS data differently. They suggested applying a multivariate analysis taking into consideration NFDPM yields that gave a significant sugar-aldehyde relationship, with an R 2 correlation equal to 34%, and they concluded that normalising for NFDPM may obscure a sugar-aldehyde relationship.…”
Section: Introductionmentioning
confidence: 99%